Treatment Options for Bilateral Autologous Breast Reconstruction in Patients with Inadequate Donor-Site Volume - Chu, Michael W.; Samra, Fares; Kanchwala, Suhail K.; Momeni, Arash (Journal of Reconstructive Microsurgery, 2017)
More than 250,000 women will be diagnosed with invasive breast cancer in the United States in 2017 alone. A large number of these patients will undergo mastectomy and will be candidates for immediate breast reconstruction. The most common reconstructive options are either implant-based or autologous tissue reconstruction, with the latter having been reported to have higher rates of long-term patient satisfaction, lower cost, and less postoperative pain. A subset of patients, however, may not be ideal candidates for autologous microsurgical reconstruction, for example, due to inadequate abdominal tissues, yet they may desire this reconstructive modality. This is particularly challenging in patients requiring bilateral reconstructions. In this article, the authors discuss the various reconstructive modalities that can be considered in patients who desire bilateral breast reconstruction, are not ideal candidates for autologous reconstruction, yet do not wish to rely solely on implant-based modalities.
Keywords: plastic surgery; microsurgery; breast implant; breast reconstruction; deep inferior epigastric perforator; TRAM; free flap